Research on Loss Characteristics Based on the Vibration Law of Granular Assembly - Shengwu Zhang; Wei Xu; Chiming Wang; Yuanran Qiu; Yuanchao Zhang; Yanan Li; Yingjie Zhang (Shock and Vibration)
Particle damping technology is a typical passive vibration damping technology. In order to further explore the energy dissipation characteristics of particle dampers under different excitation, the relationship between internal vibration state and energy dissipation is analyzed. Based on the analysis of the motion state of granular assembly inside three-dimensional cylindrical particles, the steady-state energy flow method is used to study the loss characteristics of the granular assembly with different vibration laws. The research is carried out under the condition of excitation reduced acceleration of 0–8 and excitation frequency of 0–300 Hz. The results show that the loss capacity of the particles is enhanced when the vibration state of the particles changes from solid-like to other motion states. At frequencies above 250 Hz, the particle microvibrational and intermediate-vibrational loss effects are more significant. The loss capacity of the granular assembly shows frequency-dependent characteristics and is affected by frequency and reduced acceleration. With the increase of the reduced acceleration, the loss capacity of particles is enhanced and shows a local peak effect as the frequency increases. The increase of the particle size enhances the loss ability in the microvibrational state and the intermediate-vibrational state. By changing the vibrational state, the energy dissipation capacity of particle damper can be enhanced, which may provide a new idea for designing optimal granular dampers.